Reputation and trust on online labour markets: the reputation economy of Elance. (1st April 2016) - ,; ,; ,
Abstract : This article examines profile data about 9, 593 freelancers from 121 countries active in the Design and Multimedia section of Elance, a major online labour market existing up until 2015. Using statistical analysis, the article evidences that the earnings a contractor obtains from working through Elance positively correlates with higher reputation scores and suggests that the conception of trust among actors operating on an online labour market resembles that which characterises e-commerce platforms like eBay or Amazon, where trust relations among 'strangers' are guaranteed by an algorithmic-based third party that translates feedbacks and rankings into a numerical reputation proxy.